2009
DOI: 10.1007/s12552-009-9014-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Employability of Latinos: The Roles of Ethnicity, Criminal History, and Qualifications

Abstract: Latinos are disproportionately represented among the offender population in the United States, with unemployment status a leading risk factor in Latinos returning to criminal behavior. Yet, few studies have empirically examined the employment barriers of Latino ex-offenders. The current study endeavors to begin to fill this gap by examining the role of ethnicity, criminal history, and qualifications on the employability of Latinos compared to their Anglo counterparts. After reading a description of a stock wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Furthermore, ethnic minorities who have criminal records face race-related barriers to employment that significantly hinder their employment opportunities as compared to European Americans (Pager, 2003;Varghese, Hardin, & Bauer, 2009). While 1 in 45 adult European Americans (both men and women) are under correctional supervision, the numbers are 1 in 11 for African Americans and 1 in 27 for Latinos (Pew Center on the States, 2009).…”
Section: Contextual Barriers and Supports Person Inputs And Learninmentioning
confidence: 99%
“…Furthermore, ethnic minorities who have criminal records face race-related barriers to employment that significantly hinder their employment opportunities as compared to European Americans (Pager, 2003;Varghese, Hardin, & Bauer, 2009). While 1 in 45 adult European Americans (both men and women) are under correctional supervision, the numbers are 1 in 11 for African Americans and 1 in 27 for Latinos (Pew Center on the States, 2009).…”
Section: Contextual Barriers and Supports Person Inputs And Learninmentioning
confidence: 99%
“…The Latino population has been identified as the fastest growing and most influential minority ethnic group in the United States, and it is estimated that by the year 2050, one in three individuals living in the United States will be of Latino descent (Kilgust, 2009; Stowell, Martinez, & Cancino, 2012; Varghese, Hardin, & Bauer, 2009). 1 However, Latinos’ involvement in the criminal justice system has risen more rapidly than their population growth, including those convicted of sex crimes (Smith-Socaris, Perry, & Fox-Mullen, 2006), suggesting an overrepresentation of this group within the system (Lopez & Livingston, 2009).…”
mentioning
confidence: 99%
“…Yet, Blacks were the least likely to receive training from college or trade school while in prison, as indicated by obtaining a certificate (Rampey et al, 2016). These compounded difficulties, coupled with racism, would continue the cycle of disadvantages in employment following release (Pager, 2003;Varghese, Hardin, Bauer, 2009). Relatedly, in an empirical investigation, researchers found that employers were less likely to call back Black men with a criminal record than their White counterparts, all other factors being equal (Pager, 2003).…”
Section: Adult Correctionsmentioning
confidence: 99%
“…For People of Color with a criminal background, obtaining job qualifications could reduce some employment barriers (e.g., Varghese, Hardin, & Bauer, 2009). Davis et al (2013) of the RAND Corporation found that participation in prison education programs decreased probability of recidivating by 43%.…”
Section: Empower Communities With Knowledgementioning
confidence: 99%